Aplikasi Teknologi Asap Cair dalam Pengolahan dan Pengawetan Produk Perikanan di Pulau Mandangin [ Technology Application of Liquid Smoke in Processing and Preservation of Fishery Products in The Mandangin Island] - Sapto Andriyono; Wahju Thajaningsih; Agustono Agustono; Endang Dewi Masithah; Kustiawan tri Pursetyo; Annur Ahadi Abdillah; Heru Pramono (Jurnal Ilmiah Perikanan dan Kelautan, 2015)
Abstract The increase in value-added of fishery products is one of which can be done by processing. In addition to maintaining the value of the protein in the fish raw material, it would be easier if the product is stored and increase the sale value of the fish itself. The ability to perform in the fish processing in Mandangin island is still very limited. Community service activities that have been carried out by a team of the Faculty of Fisheries and Marine Universitas Airlangga was introduce smoked fish product processing with liquid smoke,because this method easier and faster so that the products can be marketed. Liquid smoke was developed because the location is very minimal in the supply of raw materials such as firewood and coconut, so the use of liquid smoke is very appropriate. The resulting refined products are expected to be a source of protein Mandangin Island community itself and is able to become an alternative source of income for the community to increase the sale value of fishery products. Mentoring process being conducted by a team from the Faculty of Fisheries and Marine Universitas Airlangga so that the products can be marketed outside Mandangin Island or even to other areas in East Java.